2011
DOI: 10.1021/ol202056w
|View full text |Cite
|
Sign up to set email alerts
|

Total Synthesis of (−)-Leuconicine A and B

Abstract: Concise asymmetric total syntheses of Strychnos alkaloids (-)-leuconicine A (14 steps, 9% overall yield) and B (13 steps, 10% overall yield) have been accomplished. Key steps include (1) our sequential one-pot spiro-cyclization/intramolecular aza-Baylis-Hillman method to prepare the ABCE framework; (2) a novel domino acylation/Knoevenagel cyclization to prepare the F-ring; and (3) a Heck cyclization to access the D-ring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(28 citation statements)
references
References 13 publications
1
24
0
1
Order By: Relevance
“…Keywords: alkaloids · Barbier reaction · cascade reaction · indole · samarium diiodide [ Representative examples of Strychnos alkaloids. [9,10] Chem. Eur.…”
Section: Introductionmentioning
confidence: 99%
“…Keywords: alkaloids · Barbier reaction · cascade reaction · indole · samarium diiodide [ Representative examples of Strychnos alkaloids. [9,10] Chem. Eur.…”
Section: Introductionmentioning
confidence: 99%
“…Anti-cancer agents aza-epothilones A–D v (see Fig. 1a), leuconicines A–B vi , natural products that can reverse multi-drug resistance, and immunosuppressant FR235222 vii are among entities the synthesis of which involves homoallylic amines. Enantioselective addition of an allyl group to an aldimine has thus been the subject of substantial scrutiny iv .…”
mentioning
confidence: 99%
“…The use of reactive haloamides to form the C ring of aspidosperma and related alkaloids, by way of an intramolecular alkylation, is well established, having been first demonstrated by Heathcock in the synthesis of (±)-aspidospermidine. 19,20 Accordingly, we found that activation of the iodide with silver trifluoromethanesulfonate, along with added base, facilitated the desired spirocyclization, delivering the spirocyclic indolenine 13 . For formation of the E ring, we drew inspiration from Andrade’s recent exploits regarding a similar intramolecular aza-Morita–Baylis–Hillman reaction.…”
Section: Resultsmentioning
confidence: 92%
“…For formation of the E ring, we drew inspiration from Andrade’s recent exploits regarding a similar intramolecular aza-Morita–Baylis–Hillman reaction. 20,21 We were delighted to discover that addition of the highly nucleophilic and sterically undemanding trimethylphosphine to a solution of the indolenine 13 in benzene, with methanol as an additive, promoted the desired intramolecular aza-Morita–Baylis–Hillman reaction, yielding the desired pentacycle 19 in 80% yield over two steps. 22,23 …”
Section: Resultsmentioning
confidence: 99%